Do Hormones Influence Women's Sex? Sexual Activity over the Menstrual Cycle. (1st January 2014) - Caruso, Salvatore; Agnello, Carmela; Malandrino, Chiara; Lo Presti, Lucia; Cicero, Carla; Cianci, Stefano
Abstract: Introduction: In mammals, the effects of ovarian steroids influence sexual behavior. In humans, there are a few studies that take into account if ovulation occurs. Aim: The study aims to investigate if a woman's sexuality changes during the week and over the menstrual cycle, and if so, in what way. Methods: This is a prospective cohort study; 1, 957 heterosexual women were involved over the period January 2004–December 2011. Two subgroups were taken into consideration, women having a partner and singles. Main Outcome Measure: Sexual interview and the Female Sexual Function Index and Female Sexual Distress Scale questionnaires were used to exclude women with sexual dysfunction. Women with ovulation confirmed by sonography were enrolled. Women were given diary cards on which to report their daily sexual activity. Serum concentrations of estradiol, progesterone, total testosterone, sex hormone binding globulin, and free androgen index were measured during the follicular, periovular, and luteal phase of the menstrual cycle. Results: One thousand one hundred eighty women (age range 18–40 years) were included in the analyses. Of them, 925 had a heterosexual relationship and 255 were single. Women with a partner had more sexual activity during the weekend, while the singles had a constant sexual activity over the week. The sexual activity of singles was higher during the ovulatory phase and lower during menses than that of the women with a partner. A linear correlation between sexual activity and androgenic hormonal profile during the menstrual cycle in women with and without a partner was observed. Conclusions: Ovarian steroids modulate a woman's sexual activity. This aspect was more evident in singles than in women having a partner, in which a variety of nonhormonal factors can have a role.